Coexistence of a right vertebral artery originating from the right common carotid artery, an aberrant right subclavian artery and a left primitive proatlantal intersegmental artery: First case report - Jinlu Yu (Radiology Case Reports)
There are no reports of the coexistence of a right vertebral artery (VA) originating from the right common carotid artery (CCA), an aberrant right subclavian artery (SCA) and a primitive proatlantal intersegmental artery (PPIA); thus, we report such a case. A 61-year-old female presented with subarachnoid hemorrhage. Computed tomography angiography (CTA) and digital subtraction angiography (DSA) revealed a ruptured right posterior communicating artery (PcomA) aneurysm. The PcomA aneurysm was successfully embolized, and the patient recovered well. Moreover, CTA and DSA revealed that the right VA originated from the right CCA instead of the right SCA. The right SCA was aberrant from the aorta, a PPIA originated from the left external carotid artery and extended posteriorly into the left C1 transverse foramen to connect with the left intracranial VA, and the left extracranial VA was hypoplastic. Our report contributes to the literature concerning the rare variation in the origins of larger vessels located above the aorta. In addition, in our report, the complex anatomy of the neck vessels made establishing a path to access intracranial aneurysms difficult.